Analysis of unreinforced and reinforced shallow piled embankments under cyclic loading. Issue 2 (17th June 2019) - Aqoub, K.; Mohamed, M.; Sheehan, T.
Abstract : Reinforced piled embankments are being increasingly used for construction over soft ground due to their efficiency in reducing potential settlement, speed of construction, and associated cost. Most of the previous studies focused on developing understanding of the behaviour of thick embankments that are loaded with a static surcharge load. Data on the behaviour of shallow piled embankments under cyclic loadings are scarce. In this study, an experimental programme was undertaken using a fully instrumented testing rig to generate data and improve our understanding of the behaviour of unreinforced and reinforced shallow piled embankments subject to monotonic and cyclic loadings that were applied over a predetermined area of the embankment. The experimental results showed that collapse of soil arching is instantaneous and occurs during the first few cycles of load. However, strength was regained, and recovery of the arching effect was observable during further stages of cyclic loadings due to densification of the embankment material and deformation of the soft subsoil. Inclusion of reinforcement layers was found to enhance the performance of load transfer mechanisms by concentrating stresses on pile caps. The results clearly showed a significant reduction in surface settlement, soft subsoil settlement and heaving with increasing numbers of reinforcement layers.